Development of Fluorescent and Biotin Probes Targeting NLRP3 - Keuler, Tim; Gatterdam, Karl; Akbal, Anil; Lovotti, Marta; Marleaux, Michael; Geyer, Matthias; Latz, Eicke; Gütschow, Michael (Frontiers in Chemistry, 2021)
Extracellular signals drive the nucleation of the NLRP3 inflammasome which leads to the release of cytokines and causes inflammatory events. Hence, the inflammasome has gained enormous momentum in biomedical basic research. The detailed mechanisms of inflammasome generation and regulation remain to be elucidated. Our study was directed towards the design, convergent synthesis, and initial biochemical evaluation of activity-based probes addressing NLRP3. For this purpose, probes were assembled from a CRID3/MCC950-related NLRP3-binding unit, a linker portion and a coumarin 343 fluorophore or biotin. The affinity of our probes to NLRP3 was demonstrated through SPR measurements and their cellular activity was confirmed by reduction of the interleukin 1 release from stimulated bone marrow-derived macrophages. The initial characterizations of NLRP3-targeting probes highlighted the coumarin probe 2 as a suitable tool compound for the cellular and biochemical analysis of the NLRP3 inflammasome.